2020
DOI: 10.3390/su12145782
|View full text |Cite
|
Sign up to set email alerts
|

Are Non-Perennial Rivers Considered as Valuable and Worthy of Conservation as Perennial Rivers?

Abstract: Non-perennial rivers, watercourses that cease to flow at some point in time and space, are widespread globally but often lack effective protections. Although it is thought that these ecosystems are undervalued by society, empirical studies exploring people’s perceptions of non-perennial rivers are uncommon. We carried out an image-based survey at three U.S. universities to measure students’ perception of riverscapes according to seven characteristics: aesthetics, naturalness, habitat for biodiversity, habitat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…For example, swimming in IPs can be less attractive if water quality decreases with time [5], or the loss of surface flow can reduce toxic sequestration [4]. Despite all these ecosystem services, however, the social perception of IPs and their conservation value is much lower than that of the flowing phase or perennial rivers, and partly higher than that of dry riverbeds [142].…”
Section: Conservation Of Isolated Pools: Current Management Needs and Future Perspectivesmentioning
confidence: 99%
“…For example, swimming in IPs can be less attractive if water quality decreases with time [5], or the loss of surface flow can reduce toxic sequestration [4]. Despite all these ecosystem services, however, the social perception of IPs and their conservation value is much lower than that of the flowing phase or perennial rivers, and partly higher than that of dry riverbeds [142].…”
Section: Conservation Of Isolated Pools: Current Management Needs and Future Perspectivesmentioning
confidence: 99%
“…Recreational interest is supported by various studies in different cultural and geographical contexts (i.e., Belgium, Turkey, southern China, Japan). Indeed, the value that residents assign to river areas increases after the conversion of this area into a space that favors multiple uses, such as walking, cycling, or quiet contemplation [123][124][125][126]. It has been demonstrated that such life experiences improve the ecological awareness in favor of river ecosystems [110].…”
Section: Tenet 6-awareness: Promote Awareness and Education Among The Local Populationmentioning
confidence: 99%
“…Similarly, Ruiz-Villanueva et al [11] showed that people living near the Pyrenees mountains had a more positive perception about the presence of dead wood within river channels than those living in the center of the Iberian Peninsula, which has been associated with the good conservation of the rivers and forests of the Pyrenees region. In this vein, Rodríguez Lozano et al [10] found that students' perception of non-perennial streams differed between US states (Washington, California, and Arizona). More While fish were recognized as inhabitants of rivers by all educational levels, the percentage of respondents who also recognized plants, insects, and vertebrates increased with educational level.…”
Section: Differences Among Educational Levels and Territoriesmentioning
confidence: 99%
“…In fact, rivers are still frequently perceived as water channels that flow into the sea, despite current scientific knowledge [9]. Similarly, the value of the diversity of existing river ecosystems is rarely recognized [10], as well as the biotic and abiotic elements needed for their conservation [11,12].…”
Section: Introductionmentioning
confidence: 99%